Two amplicon sequencing strategies revealed different facets of the prokaryotic community associated with the anaerobic treatment of vinasses from ethanol distilleries - Martinez, Maria Alejandra (2014)
The prokaryotic consortium from a pilot-scale UASB reactor fed with vinasses from ethanol distilleries was evaluated by means of amplicon sequencing of the 16S rRNA gene. Two different sets of primers targeted to overlapping regions of the V4-16S region were used to gain a broad picture of such community and to perform a comparative analysis. From the two datasets obtained, prevalent phyla were Firmicutes, Verrucomicrobia and Thermotogae. Interestingly, one set of primers captured variability in both the bacterial and archaeal portions of the community, whilst the other one revealed a more diverse community structure, but only in the Bacteria domain. Although a certain level of agreement between the two strategies was observed, sharp differences indicate that different facets of the community were disclosed by each approach.